Detection and characterization of pineapple mealybug wilt-associated viruses 1, 2, and 3 in pineapple cultivars in Malaysia - Mohd Anuar, Intan Sakinah; Nusaibah, Syd Ali; Vadamalai, Ganesan; Mokhtar, Anis Syahirah; Sapak, Zaiton (Springer Science and Business Media Deutschland, 2025)
Mealybug wilt of pineapple (MWP) is the most devasting viral disease affecting pineapples worldwide. The mutualistic relationship between mealybugs and ant species contributes to the disease’s spread. Between July and September 2020, pineapple production fields of cultivars MD2, Josephine (Josapine), Sarawak, and Crystal Honey in Melaka, Johor, and Negeri Sembilan displayed MWP disease symptoms. Symptomatic and asymptomatic leaf samples were collected for molecular characterization of the causal pathogen. These samples were amplified using RT-PCR with specific primers to detect pineapple mealybug wilt-associated viruses (PMWaVs) -1, -2, and − 3. A total of 20.2% was detected with PMWaV-1, 44.7% with PMWaV-2, and 35.1% with PMWaV-3. Mixed infections were also detected for all the cultivars. Phylogenetic analysis of heat shock protein 70 homolog (HSP70h) and coat protein (CP) gene sequences using the neighbor-joining (NJ) approach revealed interspecific variation between the isolates among the cultivars and localities. In addition, morphological characterization was carried out to support the detection of viruses by revealing the presence of dark spots and cytopathological changes in the infected leaves. In conclusion, MWP disease among the cultivars and localities surveyed was associated with PMWaV-1, PMWaV-2, and PMWaV-3. The most common infection detected was a mixed infection of PMWaV-2 and PMWaV-3.